(untitled) - Larson, Charles U. (Belmont, 1995)
Anne Elliot is persuaded to break off an engagement to Capt. Wentworth, but tensions are resumed when they meet again eight years later.
Keywords: Persuasion (Psychology),Thuyết phục (tâm lý)